PERBANDINGAN KARAKTERISTIK AKTIVITAS SINTILASI IONOSFER DI ATAS MANADO, PONTIANAK DAN BANDUNG DARI DATA PENERIMA GPS (CHARACTERISTICS COMPARISON OF IONOSPHERIC SCINTILLATION ACTIVITIES OVER MANADO, PONTIANAK AND BANDUNG BASED ON GPS RECEIVER DATA) - Sri Ekawati; Sefria Anggarani; Dessi Marlia (Lembaga Penerbangan dan Antariksa Nasional, 2016)
Ionospheric scintillation activity on certain region need to be known its characteristics since its occurrence can degrade satellite signal quality of global satellite navigation system (GNSS) and also satellite communication that works at L-band frequency. The occurrence of ionospheric scintillation varies with location. Therefore, this paper aimed to determine comparative charasteristics of ionospheric scintillation activity over Manado, Pontianak and Bandung from amplitude scintillation index S4 data derived from GPS receiver. The data obtained from the GPS Ionospheric Scintillation and TEC Monitor (GISTM) at Manado station (1.48o N; 124.85oE geomagnetic latitude 7.7oS), at Pontianak station (0.03o S;109.33oE geomagnetic latitude 9.7oS) and at Bandung (-6.90oS;107.6oE geomagnetic latitude 16.54oS) on July 2014 to June 2015. The data were classified into three categores : quiet, moderate and strong based on s4 index. Then we calculated percentage occurrence of scintillation monthly from each observation stastions and mapping of S4 index over Manado, Pontianak and Bandung. The results show that the presentage of strong scintillation (S4>0.5) above Manado is always lower than the other stastions. Strong scintillation was detected at one stations may not also detected at other stations. For very strong scintillastion event, the occurrence of strong scintillation could be detected by all observation stastions but vary in duration. Duration of strong scintillation over Bandung was the longest (up to 4 hours) compared to Pontianak (less than 2 hours) and Manado (less than 1 hour). Based on map of distribution scintillastion occurrence, strong scintillation occurs more intensively over Bandung than over Pontianak and Manado.